An Investigation into the Aspiration Efficiency of Building Ventilation System Inlets for Reducing Energy Consumption in Air Filtration Systems - Considine, Brian (Trinity College Dublin. School of Engineering. Disc of Civil Structural & Environmental Eng, 2023)
The built environment has been widely recognised as one of the largest energy consumers in the modern world, negatively impacting the environment and contributing to climate change. A disaggregation of the energy consuming sub sectors within the built environments, attributes heating, ventilation and air conditioning (HVAC) services as the most intensive. Development of abatement strategies through technological innovations or guidelines for building services installation is vital in mitigating against climate change. In particular, natural and anthropogenic sources of particulate matter (PM) have a detrimental impact on energy consumption and indoor air quality (IAQ) in buildings. The delivery of treated air into indoor microenvironments typically involves filtration systems that trap PM. A consequence of this process is particle accumulation on the filter which increases the differential pressures across the filter as the resistance to airflow increases, incurring higher energy consumptions. The transportation of ambient PM from outdoor air into the inlet of a mechanical building ventilation system is poorly understood. No studies have examined the effect commercial air handling unit (AHU) inlet designs such as rainhoods have upon the migration of PM from the ambient environment into the building ventilation system, and implications of this on energy consumption and IAQ. Through numerical methods, the differences in concentration of PM in ambient air and that within AHUs were determined, more commonly referred to as Aspiration Efficiency (AE %). This quantity assesses the ratio of the ambient concentration to the in-AHU concentration where for a large ventilation system, an AE of 0% is most desirable in contrast to PM samplers where 100% is sought for accuracy rather than PM control. The initial study was concerned with understanding the building and environmental variables that effect this process such as wind speed, wind direction, particle diameter size and ventilation flow rates. Establishing the AE of existing AHU inlet designs, the dynamics of PM concentrations passing from the ambient environment to indoor spaces can be used in the creation of novel PM control technology known as aspiration efficiency reducers (AERs). We also aimed to create the baseline AE of existing rainhoods, which have not be designed with PM control in mind, but nevertheless possess an AE. Results found facing the AHU inlets away from the particle laden wind resulted in substantially different filter loading rates across a range of particle diameters. This study was followed by developing sustainable AERs to reduce the ambient PM concentration entering an AHU, and minimise filter loading in order to reduce the energy consumed, increase filter lifespan and an improve IAQ. Results showed that AERs could reduce AE for PM10 concentrations by 5-35%, corresponding to 3.2-9.3% energy savings compared to commercial rainhoods. Furthermore the project was also concerned with expanding our understanding of how PM2.5 emissions from local traffic pollution sources impacts on filter loading. Considering the AHU rooftop location and orientation relative to the wind, and the PM source could lead to further optimisation of ventilation systems performance. This study found that increasing the distance from the local source reduces PM filter loading for an AHU inlet facing into the wind. Rotating the inlet away from the prevailing wind results in the lowest AE. Finally field tests in an urban environment have been performed on the AER attachments designed and compared with a control AHU using a commercial rainhood. The pressure drop across both an ePM1 70% fabric bag filter and a coarse 60% efficiency panel filter was monitored in addition to the system pressure and compared. Results show that AER technology resulted in a reduction in filter loading.
APPROVED
Keywords: Aspiration efficiency; CFD; Energy efficiency; Particulate matter; Ventilation